2013
DOI: 10.1007/s10144-013-0396-z
|View full text |Cite
|
Sign up to set email alerts
|

Polar bear predatory behaviour reveals seascape distribution of ringed seal lairs

Abstract: Ringed seal (Pusa hispida) breeding distribution has been extensively studied across near‐shore habitats, but has received limited attention at a seascape scale due to the difficulty in accessing offshore sea ice environments. Employing highly visible predation attempts by polar bears (Ursus maritimus) on ringed seals in subnivean lairs observed by helicopter, the spatial relationship between predatory behaviour and ringed seal breeding habitat was examined. Resource selection functions were used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…Similar to our results, Mauritzen et al [12] found that the probability of using high sea ice concentrations decreased when bears were located in areas with high sea ice concentrations, but exhibited the opposite pattern when bears were in areas with low concentrations of sea ice. Polar bears live in a highly dynamic environment, requiring them to respond by constantly moving to areas with conditions suitable for finding and capturing prey [16,36]. The lack of change in functional responses between periods implies that polar bears are making similar decisions in response to their local conditions as they did before sea ice changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our results, Mauritzen et al [12] found that the probability of using high sea ice concentrations decreased when bears were located in areas with high sea ice concentrations, but exhibited the opposite pattern when bears were in areas with low concentrations of sea ice. Polar bears live in a highly dynamic environment, requiring them to respond by constantly moving to areas with conditions suitable for finding and capturing prey [16,36]. The lack of change in functional responses between periods implies that polar bears are making similar decisions in response to their local conditions as they did before sea ice changes.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also focus on relating polar bear space use to ice metrics that are more directly related to seal presence and abundance (e.g. presence/absence of pressure ridges; [16]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although that explanation seems reasonable given both the current and historical distributions of these various predators, the relative importance of polar bear predation is uncertain because of the confounding influence of aboriginal peoples in the Arctic. It appears, however, that the distribution of ringed seal lairs is driven at least partially by the risk of predation from polar bears (102).…”
Section: Pinnipedsmentioning
confidence: 99%
“…The influence of ringed seal whelping was also observable at inter-annual scales, with total kill frequency positively correlated to years of high ringed seal natality, whereas adults were killed in higher proportion in years when natality was low. Employing locations of seal kills and attempted hunts at ringed seal subnivean lairs, Pilfold et al (2013) showed that polar bears selected for active areas of sea ice near the floe edge when hunting. Ringed seal whelping areas were located over a range of habitats, and the distribution was correlated with their natality rates.…”
Section: Polar Bear Foraging Ecology In the Beaufort Seamentioning
confidence: 99%